Generating Radiofrequency Ablation Lesions Using Magnetically Coupled Bipolar Catheters. - Lee, Choonghee; Choi, Eue-Keun; Kong, Hyoun-Joong; Choy, Young Bin; Kim, Hee Chan; Oh, Seil (Pacing & Clinical Electrophysiology, 2011)
Background: Transmural lesions are difficult to produce in myocardial regions with thick walls, such as the left ventricle (LV), using conventional radiofrequency (RF) ablation catheters. This study was performed to evaluate the efficacy of magnetically coupled bipolar catheters and compare the performance with conventional unipolar and bipolar RF ablation catheters. Methods and Results: Neodymium magnets assembled in ablation catheters were used to facilitate tissue contact in a bipolar RF ablation system. In vitro sheets of porcine skeletal muscle, with 10-mm thickness, were ablated with a 4-mm-tip unipolar RF ablation catheter (UA), a bipolar ablation system (BA) using a pair of 4-mm-tip catheters, and a magnetically coupled bipolar system (MB). The RF generator setting was 50 W and 90°C. RF energy was delivered for 30 or 60 seconds and five lesions were created in each ablation condition. The bottom side of the skeletal-muscle sheet was exposed to saline at 37°C and a flow of 5.6 L/min, mimicking the LV endocardial surface. The top side was exposed to air, mimicking the epicardial surface. In the 60-second ablation cases, the transmuralities were 0%, 0%, and 40% (UA, BA, and MB, respectively). The volumes of the lesions were 61.5 ± 8.5, 224.3 ± 51.8, and 359.3 ± 93.8 mm3 (UA, BA, and MB, respectively). Conclusions: The magnetically coupled bipolar RF ablation system created transmural lesions more efficiently than the conventional ablation system, primarily due to higher RF current density and stronger tissue contact. This prototype method could be applied to the development of novel ablation devices for thick areas of tissue. (PACE 2011; 34:934-938)